PERLUASAN JANGKAUAN AUDIENS TELEVISI MELALUI MEDIA SOSIAL (STUDI KASUS LIVE STREAMING PROGRAM BERITA MALAM METRO TV DI TIKTOK) - Alfarel Prapto Wibowo; Makroen Sanjaya (Jurnal Ilmiah Multidisiplin Ilmu, 2026)
The development of digital technology has shifted media consumption patterns from conventional television to digital platforms such as TikTok. This change requires television stations to adapt their content distribution strategies to remain relevant and maintain audience engagement. Metro TV utilizes the TikTok live streaming feature to expand the reach of its evening news program and attract digital audiences. This study aims to analyze how Metro TV expands its audience reach through live streaming on TikTok and how interaction with digital viewers is formed.This research uses a qualitative method with a case study approach. Data were collected through in-depth interviews, observation, and documentation. The study focuses on the strategy used by Metro TV in adapting television news content into digital formats suitable for TikTok.The results show that Metro TV modifies television content into shorter, lighter, and more interactive formats that match the characteristics of TikTok users. Live streaming also enables real-time interaction through comments and live chat features. These interactions create two-way communication between broadcasters and audiences, which increases engagement and audience loyalty. The study concludes that live streaming on TikTok is an effective strategy to expand television audience reach, particularly among younger generations who increasingly consume news through digital platforms.